2019
DOI: 10.3389/fimmu.2019.01436
|View full text |Cite
|
Sign up to set email alerts
|

Omp19 Enables Brucella abortus to Evade the Antimicrobial Activity From Host's Proteolytic Defense System

Abstract: Pathogenic microorganisms confront several proteolytic events in the molecular interplay with their host, highlighting that proteolysis and its regulation play an important role during infection. Microbial inhibitors, along with their target endogenous/exogenous enzymes, may directly affect the host's defense mechanisms and promote infection. Omp19 is a Brucella spp. conserved lipoprotein anchored by the lipid portion in the Brucella outer membrane. Previous work d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Surprisingly, the functional aspects of proteases in Brucellae have not been investigated with proteomics so far. This is in sharp contrast to the proven importance of proteases for a great many functions such as host infection and persistence [89][90][91][92], stress response [92][93][94][95][96], morphology [97], communication and signaling [98][99][100], to name the most prominent.…”
Section: Proteases-a Yet Untouched Topic In Proteomics For Brucellamentioning
confidence: 84%
“…Surprisingly, the functional aspects of proteases in Brucellae have not been investigated with proteomics so far. This is in sharp contrast to the proven importance of proteases for a great many functions such as host infection and persistence [89][90][91][92], stress response [92][93][94][95][96], morphology [97], communication and signaling [98][99][100], to name the most prominent.…”
Section: Proteases-a Yet Untouched Topic In Proteomics For Brucellamentioning
confidence: 84%
“…At present, some experiments have shown that Omp10, Omp19, Omp25, and Omp31 are involved in Brucella virulence (11)(12)(13). The Brucella Omp19, Omp25, and Omp31 mutant were attenuated in cellular models and in mice, indicating that Omp19 and Omp25 were important for bacterial survival in vitro and in vivo (11,(14)(15)(16)(17). Furthermore, Omp25 and Omp31 disrupt the immune response by regulating the secretion of tumor necrosis factor alpha (TNF-α) expression and apoptosis in porcine and murine macrophages infected models (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Omp19 is a surface-exposed lipoprotein broadly expressed within the Brucella genus, which plays an active role in bacterial cell adhesion, cell invasion, colonization, immune modulation, and intracellular survival (Figure 5 A) [ 48 ]. It has demonstrated that Omp19 is a possible vaccine candidate and has adjuvant activity as protease inhibitor, which can be used as positive control [ 49 , 50 ]. VirB8 from Brucella is a bitopic inner membrane protein, which undergoes several protein–protein interactions that have an impact on both the functionality and assembly of the T4SS complex, suggesting a key role in the T4S system (Figure 5 B) [ 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%